Palabra de hidalgo, espejo de rey. Acerca de un episodio de la Crónica de D. Fernando de Fernão Lopes - Arsenio Dacosta (Medievalista)
From two allusions in Fernão Lopes’ Crónica de D. Fernando, it is attempted to explain the presence in Portugal of a Biscayan nobleman, Juan Alonso de Múgica, during the reign of Ferdinand I. Beyond the purely prosopographic work, this study uses the contents of the chronicle to delve into the treatment of concepts like counsel and royal liberality in political contexts of intense propagandistic construction as were the Portuguese and Spanish courts of the late 14th and early 15th centuries. It addresses, in short, the archetype of the king in Portugal and Castile in the historiography of both kingdoms, finding significant parallels and transfers, as well as the emergence of class discourses in the urban elites and the nobility.